Fine mapping of a locus presumably involved in hybrid inviability (HIs-1) between flowering cherry cultivar Cerasus × yedoensis ‘Somei-yoshino’ and its wild relative C. spachiana - Tsuruta, Momi (Breed Sci, 2019)
Flowering cherry is an extremely renowned ornamental tree, consisting of a variety of species and cultivars. Because cherry species have no strict barriers for interspecific hybridization before fertilization, identification of the gene underlying post-zygotic hybrid inviability will help breeders identify specimens for breeding and help us understand speciation mechanisms. In this study, we mapped the genetic linkages and physical genome sequences for a presumed hybrid inviability locus (HIs-1) that we observed in the seedlings crossed between Cerasus × yedoensis ‘Somei-yoshino’ and its wild relative C. spachiana. By the surveying linkage maps of ‘Somei-yoshino’ and C. spachiana, we identified correlation with seedling inviability only in linkage group 4 (LG4) of the ‘Somei-yoshino’ map. When we produced a finer-scaled map of HIs-1 in LG4, we found that HIs-1 is located between two microsatellite (SSR) markers with a 3.8 cM span. Using eight SSR markers based on peach genome sequences, we further refined the candidate region for HIs-1. This region was located between Pp04C001 and Pp04C007 markers, spanning 240 Kb of the peach genome, in which 45 transcribed genes had been estimated. From these candidate genes, it will be feasible to identify molecular mechanisms involved in cherry hybrid inviability.